The Effect of Dietary Protein and Water Temperatures on Performance of T. rendalli Juveniles Reared in Indoor Tanks - Musuka, C.G.; Likongwe, J.S.; Kang 'ombe, J.; Jere, W.W.L.; Mtethiwa, A.H. (Pakistan Journal of Nutrition, 2009)
An experiment was conducted at Bunda College of Agriculture, Lilongwe, Malawi for 14 weeks (from August to November 2005) to determine the combined effect of dietary protein (30 and 40%) and water temperatures (22.8, 26 and 30 °C) on the performance of Tilapia rendalli juveniles reared in eighteen 200-L tanks with stocking rates of 15 fish (average wt 9.25g/fish) per tank. Results showed that the treatment of 40% crude protein at 30 °C temperature produced significantly (p<0.05) greater growth, with a weight gain of 220.55%. Whole body moisture, protein and ash content increased and differences among treatments were highly significant (p<0.05) among treatments. Whole body lipid decreased in the treatment with 40% crude protein fed at 26 °C, while moisture, protein, ash and energy increased in all treatments. Blood glucose and haematocrit values did not differ significantly across all treatments. Dietary protein and water temperature significantly influenced changes in body weight, Specific Growth Rate (SGR) and feed conversion ratio of T. rendalli. The experiment showed that high dietary protein and water temperature produced the best feed conversion ratio (FCR) of 2.74, but this was still higher than that recommended by many researchers. Temperature in particular, had a significant effect on the growth of T. rendalli at different dietary protein levels. Growth of fish increased with an increase in dietary protein and water temperature. Survival was over 90% across treatments.